Glacier Retreat and Pro Glacial Lake dynamics of Darma Valley, Central Himalaya, India - Reza, Masoom; Joshi, Ramesh Chandra; Nabiyal, Chandra; Negi, Mamta (Bulletin of Geography. Physical Geography Series, 2023)
The physiography and climate of the higher Himalaya are unique in nature. Some phenomenal changes that are dynamic and become inevitable due to global temperature rise, such as variability of glacier cover, lake area and glacier retreat. This study is conducted using remote sensing data. A total of 17 glaciers are mapped using Sentinel-2 (2020), Landsat 5 (1994), and Corona declassified (1966) data. In 1966, the total area of glaciers was 74.309 ± 0.1478 Km2, which decreased to 72.072 ± 0.370 Km2 in 2020. The estimated total loss of glacier area in 54 years (1966-2020) is 2.236 ± 0.016 Km2. The average total retreat of the terminus in 54 years is 439.30 ± 13.795 m and the annual retreat is 7.91 ± 0.255 m. In the same valley, 6 (six) major glacial lakes were also observed, with the most expanding lake GLK – 5 expanding by 2010.7 ±30.26% in 54 years.